1999
DOI: 10.1111/j.1471-6402.1999.tb00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Disordered Eating Among Asian American and Caucasian College Students

Abstract: Using a sample of Caucasian and Asian American college students, this research examined gender differences within race and race differences within gender with respect to a wide range of body image and disordered eating variables. Results indicated that: (a) regardless of race, women reported more problem attitudes and behaviors than did men; (b) gender differences were similar for Asian Americans and Caucasians, although Caucasians evidenced slightly more gender differences than did Asian Americans; (c) for me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
120
4
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(133 citation statements)
references
References 29 publications
(52 reference statements)
8
120
4
1
Order By: Relevance
“…This finding on gender differences supports the existing literature that indicates women exhibit more disordered eating problems compared to men, and men are less likely to develop and engage in disordered eating behaviors. 4,11 The majority of prior studies report no association between acculturation and eating disorders. 1,4,5 Our results show that the associations across several acculturation measures did not reach statistical significance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding on gender differences supports the existing literature that indicates women exhibit more disordered eating problems compared to men, and men are less likely to develop and engage in disordered eating behaviors. 4,11 The majority of prior studies report no association between acculturation and eating disorders. 1,4,5 Our results show that the associations across several acculturation measures did not reach statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…4,11 The majority of prior studies report no association between acculturation and eating disorders. 1,4,5 Our results show that the associations across several acculturation measures did not reach statistical significance. However, our analyses also show that age is strongly associated with BED and BE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Milligan and Pritchard (2006) found that among Division I collegiate athletes, more female than male athletes displayed disordered eating behaviors as evidenced by higher scores on the Eating Attitudes Test (see also Johnson, Crosby et al, 2004). Similarly, female undergraduates report lower levels of satisfaction with several specific body parts and are more likely to utilize a variety of weight-loss strategies than are their male counterparts (Kashubeck-West, Mintz, & Weigold, 2005; see also Mintz & Kashubeck, 1999). In fact, in a study of factors predicting disordered eating in college students, gender was the primary predictor of drive for thinness and body dissatisfaction, and was also a predictor of bulimic behaviors as measured by the Eating Disorders Inventory (Shea & Pritchard, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Research also shows that DE is pervasive across gender (Lavender & Anderson, 2010;Striegel-Moore & Bulik, 2007) and ethnic background (Mintz & Kashubeck, 1999;Rogers Wood & Petrie, 2010).…”
Section: Psychological Flexibility and Self-concealment As Predictorsmentioning
confidence: 99%